CTX-M Enzymes: Origin and Diffusion - Canton, Rafael; Gonzalez-Alba, Jose Maria; Galán, Juan Carlos (Frontiers in Microbiology, 2012)
CTX-M β-lactamases are considered a paradigm in the evolution of a resistance mechanism. Incorporation of different chromosomal blaCTX-M related genes from different species of Kluyvera has derived in different CTX-M clusters. In silico analyses have shown that this event has occurred at least nine times; in CTX-M-1 cluster (3), CTX-M-2 and CTX-M-9 clusters (2 each), and CTX-M-8 and CTX-M-25 clusters (1 each). This has been mainly produced by the participation of genetic mobilization units such as insertion sequences (ISEcp1 or ISCR1) and the later incorporation in hierarchical structures associated with multifaceted genetic structures including complex class 1 integrons and transposons. The capture of these blaCTX-M genes from the environment by highly mobilizable structures could have been a random event. Moreover, after incorporation within these structures, β-lactam selective force such as that exerted by cefotaxime and ceftazidime has fuelled mutational events underscoring diversification of different clusters. Nevertheless, more variants of CTX-M-enzymes, including those not inhibited by β-lactamase inhibitors such as clavulanic acid (IR-CTX-M variants), only obtained under in in vitro experiments are still waiting to emerge in the clinical setting. Penetration and the later global spread of CTX-M producing organisms have been produced with the participation of the so called “epidemic resistance plasmids” often carried in multidrug resistant and virulent high risk clones. All these facts but also the incorporation and coselection of emerging resistance determinants within CTX-M producing bacteria, such as those encoding carbapenemases, depict the currently complex pandemic scenario of multi-drug resistant isolates.